Importance of Entrepreneurship Development in Uzbekistan - Nodirovna, Mirzayeva Shirin; Hakim oʻg‘li, Narzullaev Bexruz; Karim qizi, Umurzoqova Sevinch (Journal of Innovation in Education and Social Research, 2024)
Human activity is different and directed in different directions. Entrepreneurship has a special place among them. In an economy based on market relations, entrepreneurial ability is an economic resource and necessarily requires the provision of necessary conditions. During the reforms carried out in our republic, especially at its current stage, special attention is being paid to the development of entrepreneurship, to give it wide freedom, and to eliminate any obstacles and restrictions that may hinder its development.